(untitled) (Studia theodisca, 2024)
This paper aims to investigate the relevance of Sharon Dodua Otoo’s debut novel Adas Raum in the ongoing Historikerstreit 2.0. Relevant to this new historical dispute is the possible connection between colonialism and the memory of the Holocaust. As I will show, Adas Raum seems to respond artistically to critical suggestions proposed by Michael Rothberg who interprets the link between memory and identity in a complex way, which results in non-competitive participation in collective memory construction in multi-ethnic societies and redefines the relevance of such categories as victims and perpetrators.